175k views
2 votes
Write a two-step equation involving multiplication and subtraction that

has a solution of x = 7.​

User Qdot
by
4.6k points

1 Answer

0 votes

Answer:

One answer: 3(2x + 10) - 2(x - 2) - 59 = 3

Explanation:

First, break up 7 into two parts:

3 + 4 = 7

Then, replace 7 with x:

3 + 4 = x

Then, create more complexity:

3 + 21 - 14 = x

21-14 = x - 3

3(x) - 2(x) - x = 3

Drop the last -x and add a constant:

3(2x + 10) - 2(x - 2) - 59 = 3

Proof:

3(2(7) + 10) - 2(7 - 2) - 59 = 3

3(14 + 10) - 2(5) - 59 = 3

3(24) - 10 -

72 - 10 - 59 = 3

62 - 59 = 3

3 = 3

Hope this helps! Have an awesome day! :-)

User Jlarsch
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.